Electronic Sports Media, and Political Factors in the Phenomenon of Growing Violence in Stadiums: a Semiological Reading of a Sample of Sports Media Pages (Twitter Platform - as a Model) - Sana Chabi; Sarra Rehaili; Meriem Balta (Social Empowerment Journal, 1970)
This study aims to address the phenomenon of the growing sports media violence in the digital space in light of the political changes via the “Twitter” platform, through tweets and publications of sports media, within a number of indications, symbols and meanings that constitute violence by them consciously or unconsciously. We seek in our research paper with a descriptive semiological methodology on a sample of the personal and official Twitter pages of the media, Hafid Darradji and Issam Al-Shawali as a model for interpreting the phenomenon of violence in sports stadiums, and their relationships with to the political contexts which are based on the reality of its spread and prevalence. This makes us able to study and understand voilence manifestations and growth, so that we can develop solutions and recommendations for this study.